'There's a Catch-22' – The complexities of pain management for people with advanced dementia nearing the end of life: A qualitative exploration of physicians' perspectives. (September 2017) - De Witt Jansen, Bannin; Brazil, Kevin; Passmore, Peter; Buchanan, Hilary; Maxwell, Doreen; McIlfatrick, Sonja J; Morgan, Sharon M; Watson, Max; Parsons, Carole
Background: Pain management is a cornerstone of palliative care. The clinical issues encountered by physicians when managing pain in patients dying with advanced dementia, and how these may impact on prescribing and treatment, are unknown. Aim: To explore physicians' experiences of pain management for patients nearing the end of life, the impact of these on prescribing and treatment approaches, and the methods employed to overcome these challenges. Design: Qualitative, semi-structured interview study exploring barriers to and facilitators of pain management, prescribing and treatment decisions, and training needs. Thematic analysis was used to elicit key themes. Setting/participants: A total of 23 physicians, responsible for treating patients with advanced dementia approaching the end of life, were recruited from primary care ( n = 9), psychiatry ( n = 7) and hospice care ( n = 7). Results: Six themes emerged: diagnosing pain, complex prescribing and treatment approaches, side effects and adverse events, route of administration, importance of sharing knowledge and training needs. Knowledge exchange was often practised through liaison with physicians from other specialities. Cross-speciality mentoring and the creation of knowledge networks were believed to improve pain management in this patient population. Conclusion: Pain management in end-stage dementia is complex, requiring cross-population of knowledge between palliative care specialists and non-specialists, in addition to collateral information provided by other health professionals and patients' families. Regular, cost- and time-effective mentoring and ongoing professional development are perceived to be essential in empowering physicians to meet clinical challenges in this area.